The market value between the two dilemmas of profit distribution and retention: an analytical study in the Iraqi stock market (Journal of Accounting and Financial Studies ( JAFS ), 2023)
Abstract:             The distribution or retention of profits is the third decision among financial management decisions in terms of priority, whether at the level of theory or practice, as the issue of distribution or retention is multi-party in terms of influence and impact, as determining the optimal percentage for each component is still the subject of intellectual debate because these decisions are linked to the future of the organization and several considerations, The research focus on the nature of the policies followed by the Iraqi banking sector As the sample chosen by the intentional sampling method was represented by the Commercial Bank of Iraq, Baghdad, Babylon and National of Iraq for period (2014-2021). as the data related to the research sample was tested in the light of the hypotheses using panel data, which indicated that there is no relationship between the distribution and retention policies on the market value. The weights related to the elements of distribution and retention were modified by assuming the stability of the organization's desire to maximize the owners wealth by using the genetic algorithm to provide a set of weights that maximize the value of the objective function (market value). The scientific contribution in the light of the knowledge gap, and accordingly, the idea of re-weighing the elements of distribution and retention was presented to maximize the market value, and on the other hand, it was proven that the Iraqi banking sector belongs to the irrelevance school.